Evaluating the safety and efficacy of zuranolone in the management of major depressive disorder and postpartum depression, with or without concurrent insomnia: a rigorous systematic review and meta-analysis - Raja, Adarsh; Ahmed, Saboor; Basit Ali Siddiqui, Muhammad; Lamiya Mir, Syeda; Kumar, Rakesh; Ahmed, Muhammad; Raja, Sandesh; Bin Amin, Shafin; Alim Ur Rahman, Hafsah; Deepak, Fnu; Asghar, Muhammad Sohaib (Frontiers in Psychiatry, 2024)
Major depressive disorder (MDD), postpartum depression (PPD), and insomnia are neuropsychological conditions in which zuranolone is used to improve symptoms and prognosis of the disorder. This meta-analysis aimed to determine the efficacy of zuranolone in comparison to other drugs used for treating these conditions.This meta-analysis included patients aged between 18 and 75 years who were diagnosed with major depressive disorder and postpartum depression with or without insomnia and were administered zuranolone for treatment. Only randomized controlled trials (RCTs) were included, and animal studies were excluded. The databases used were PubMed, Scopus, Cochrane, and Clinicaltrials.gov, with MeSH terms and relevant keywords for (Zuranolone) and (Depression). The Cochrane risk of bias tool was used for quality assessment.The meta-analysis included eight RCTs that analyzed data from 2031 patients. The meta-analysis revealed statistically significant changes in the Hamilton Depression Rating Scale (HAM-D), Montgomery-Åsberg Depression Rating Scale (MADRS), Hamilton Anxiety Rating Scale (HAM-A), and treatment-emergent adverse effects (TEAE) scores in the PPD subgroup. HAM-D and TEAEs scores were also significant in the MDD subgroup, but the changes in the MADRS, HAM-A, and Bech-6 scores were insignificant. Serious adverse events were insignificant in all subgroups.Meta-analysis found a significant improvement in depressive symptoms with zuranolone treatment, especially on day 15. This suggests that zuranolone is a promising therapeutic option for patients with MDD and PPD with or without insomnia.